Human rights in the United States beyond exceptionalism - Hertel, Shareen; Libal, Kathryn, 1968- (Cambridge University Press, 2011)
"This book brings to light emerging evidence of a shift toward a fuller engagement with international human rights norms and their application to domestic policy dilemmas in the United States"--